2019
DOI: 10.2139/ssrn.3480392
|View full text |Cite
|
Sign up to set email alerts
|

The Anatomy of Police Legitimacy: Dialogue, Power and Procedural Justice

Abstract: We argue that while it has the potential to direct legitimacy research along paths hitherto poorly explored, there is a need for conceptual refinement and development in three key respects. First, through recognition of micro-and meso-levels of legitimation. Second, acknowledgment that police claims-making is contingent on the authorization and endorsement of other actors. Third, a fuller consideration of the qualified role of dialogue-i.e. communication between police and policed-in public audiences' legitima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…In addition, this study suggests that police officers cannot be simply conceptualised as fixed power-holders by virtue of their societal position (Bottoms and Tankebe, 2012). Rather, our interviewees’ talk suggested that power emerges and functions within interactions between ‘citizens’, police officers and other criminal justice agents in nuanced ways (Martin and Bradford, 2019), and we report here instances of police officer disempowerment . Given this, it is important not to conceptualise police officers as de facto power-holders since feelings of disempowerment may have implications for how officers engage and interact with ‘the public’.…”
Section: Discussionmentioning
confidence: 68%
“…In addition, this study suggests that police officers cannot be simply conceptualised as fixed power-holders by virtue of their societal position (Bottoms and Tankebe, 2012). Rather, our interviewees’ talk suggested that power emerges and functions within interactions between ‘citizens’, police officers and other criminal justice agents in nuanced ways (Martin and Bradford, 2019), and we report here instances of police officer disempowerment . Given this, it is important not to conceptualise police officers as de facto power-holders since feelings of disempowerment may have implications for how officers engage and interact with ‘the public’.…”
Section: Discussionmentioning
confidence: 68%
“…In democratic contexts, contemporary police forces remain key actors in the political economy of modern state ruling, within which they act as a channelling and redistributive mechanism for the changing configurations of diverse interests and agendas (Bowling et al, 2019). Police are a state agency disciplined by the powerful, but also part of the broader political processes and conflicts in which they can stake their own claims and on which they can leave their own mark through the exercise of power and politics that policing work entails (Bowling et al, 2019; Martin and Bradford, 2019). This includes their potential to actively shape elements of their political environment and systems of government within which they operate, ranging from the making and maintenance of democracies (Aitchison and Blaustein, 2013; Bayley, 1969) to campaigning on police resources and priorities (Bowling et al, 2019) and resisting government-imposed reforms (Leishman et al, 1995).…”
Section: The Contested Public Services and The Police Conundrummentioning
confidence: 99%
“…Moreover, to tackle these ‘value conflicts and moral ambivalence’ as ‘street-level bureaucrats’ (Hoggett, 2006; Lipsky, 2010), police officers are vested by the state with specific powers. These include the use of significant symbolic, coercive and sometimes deadly force, ‘mandated as [police] are with the value laden task of maintaining order in an ever-changing society’ (Martin and Bradford, 2019:7).…”
Section: The Contested Public Services and The Police Conundrummentioning
confidence: 99%
“…As Barker argues, legitimation involves the work of justifying one's identity as a figure of authority and therefore can be better examined through authorities' discourses and practices. These examinations benefit from "backstage" contexts, where frontline actors tell stories which serve to protect and enhance their status, but also justify their moral authority and worth (Martin and Bradford, 2019). As Reus-Smit (2007) argues, the "social constituency" and the realm of political action in which legitimacy claims take place shed important light on the legitimation process.…”
Section: Narratives Of Legitimationmentioning
confidence: 99%